2013
DOI: 10.4103/0972-5229.123448
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns of physiotherapists in neonatal intensive care units: A national survey

Abstract: Objective:To determine practice pattern of physiotherapists in the neonatal intensive care units (ICUs) in India with regards to cardiopulmonary and neuromuscular physiotherapy.Materials and Methods:A cross-sectional survey was conducted across India, in which 285 questionnaires were sent via e-mail to physiotherapists working in neonatal intensive care units.Results:A total of 139 completed questionnaires were returned with a response rate of 48.7%, with a majority of responses from Karnataka, Maharashtra and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Along with chest physiotherapy, other physiotherapy practice patterns were also adopted to prevent and to treat musculoskeletal and neurological disorders in NICU. [ 6 ] In a study by Chokshi et al .,[ 4 ] it was observed that 50% of physiotherapists in India always performed chest physical therapy and only 30% of them performed neuromuscular physiotherapy in NICU. [ 4 ] In our study, we only included neurological physiotherapy interventions instead of muscular physiotherapy interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with chest physiotherapy, other physiotherapy practice patterns were also adopted to prevent and to treat musculoskeletal and neurological disorders in NICU. [ 6 ] In a study by Chokshi et al .,[ 4 ] it was observed that 50% of physiotherapists in India always performed chest physical therapy and only 30% of them performed neuromuscular physiotherapy in NICU. [ 4 ] In our study, we only included neurological physiotherapy interventions instead of muscular physiotherapy interventions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] In a study by Chokshi et al .,[ 4 ] it was observed that 50% of physiotherapists in India always performed chest physical therapy and only 30% of them performed neuromuscular physiotherapy in NICU. [ 4 ] In our study, we only included neurological physiotherapy interventions instead of muscular physiotherapy interventions. Neurological physiotherapy interventions are also important as much as chest physical therapy in NICU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeni doğan yoğun bakım ünitesindeki YBÜ pratiği-ne ilişkin aşağıdaki veriler Hindistan'ı yansıtan, bununla birlikte dünyada da benzer biçimde başvurulan yaklaşımları göstermektedir (22).…”
Section: Yeni Doğan Yoğun Bakım üNitesinde Göğüs Fizyoterapi Yaklaşımunclassified